First-Line Tyrosine Kinase Inhibitors Combined With Local Consolidative Radiation Therapy for Elderly Patients With Oligometastatic Non-Small Cell Lung Cancer Harboring EGFR Activating Mutations - Hu, Xiaolong; Li, Hongqi; Kang, Xiaoli; Wang, Xuan; Pang, Haifeng; Liu, Chen; Zhang, Jianchun; Wang, Yingjie (Frontiers in Oncology, 2022)
Objective The aim of this study was to investigate the efficacy and safety of combined applications of local consolidative radiation therapy (LCRT) and first-line tyrosine kinase inhibitors (TKIs) for the treatment of primary tumors and oligometastatic sites in oligometastatic NSCLC harboring Epidermal Growth Factor Receptor (EGFR) activating mutations. Patients and Methods Elderly patients with oligometastatic NSCLC (≤5 metastases) harboring EGFR activating mutations at the time of diagnosis were identified. They were treated with first-line TKIs alone or in combination with LCRT. Progression‐free survival (PFS) and overall survival (OS) were estimated through the Kaplan–Meier method. Results A total of 122 elderly patients were enrolled between February 2010 and January 2018. Among them, 41.0% (n = 50) received TKIs combined with LCRT (TKIs + LCRT group), whereas 59.0% (n = 72) received TKIs monotherapy (TKIs alone group). Patients were followed up for a median length of 34 months (ranging from 7.0 to 64 months). The median PFS in TKIs + LCRT group was 17 months (95%CI: 15.37–18.63), which was significantly longer than that of the TKIs-alone group (12 months; 95%CI: 11.05–12.95) (p <0.001). Median OS in TKIs + LCRT group was 38 months (95%CI: 35.61–40.39), while that of the TKIs-alone group was 29 months (95%CI: 26.86–31.14) (p <0.001). Multivariate analyses revealed that LCRT, one to two metastases, and good ECOG PS were independent predictors for better PFS (p <0.001, p = 0.004, and p = 0.027). Moreover, LCRT, good ECOG PS, and T1-2 stage were independent predictors for better OS (p <0.001, p = 0.007 and p = 0.007). Most of the patients suffered from grade 1 to 2 toxicities, and treatment-related deaths were not recorded. Conclusion First-line TKIs combined with LCRT may improve survival outcomes for elderly patients with oligometastatic NSCLC harboring EGFR activating mutations. This approach was not associated with much toxicity, therefore, it can be used for the treatment of elderly patients with oligometastatic disease.